Combined effects of predator odor and alarm substance on behavioral and physiological responses of the pearl cichlid - Arvigo, Alexandre Luiz [UNESP]; Miyai, Caio Akira [UNESP]; Sanches, Fábio H.C.; Barreto, Rodrigo Egydio [UNESP]; Costa, Tânia Marcia [UNESP] (Elsevier, 2019)
Several fish species trigger defensive behavioral responses when exposed to chemical cues that indicate predation risk. In these situations, physiological adjustments are also necessary to prepare the organism for a defensive response and increase survival odds. Chemical cues may be derived from predator odor or injured conspecifics. However, little is known about the effects of both cues combined. Therefore, our study evaluated the combined effects of predator odor (PO) and conspecific alarm substance (CAS) on the anti-predatory responses of the pearl cichlid (Geophagus brasiliensis). We set 4 experimental conditions 1) PO + CAS; 2) PO + Distilled Water (DW); 3) DW + CAS; and 4) DW + DW (negative control). Fish exposed to DW + CAS had values of ventilation rate and feeding latency significantly higher than when exposed to the other conditions, which yielded similar responses for both variables. Our data show that the combination of PO + CAS interfered with pearl cichlid behavior and physiology since it abolished CAS defensive responses. These results show that CAS plays an important role on the defensive responses of pearl cichlids, while PO does not, given that fish did not respond to PO by itself. Our findings point to different cue-specific strategies in pearl cichlids when dealing with different chemical cues that indicate predation risk.
Keywords: Alarm substance; Chemical communication; Defensive response; Geophagus brasiliensis; Predation risk; Predator odor